Od powstańczej euforii do goryczy rozczarowania – powstania śląskie według Kazimierza Kutza (PDF 462 KB) (Książnica Śląska, 2025)
The article aims to outline the issue of the Silesian Uprisings and thePlebiscites in the cinematic output of Kazimierz Kutz as well as discuss them across the spectrum of the director’s worldview evolution,with particular attention to the movie triptych: Sól ziemi czarnej (Saltof the Black Earth), 1969; Perła w koronie (Pearl in the Crown), 1971;Paciorki jednego różańca (The Beads of One Rosary), 1979. Over theyears, Kutz completed his initial vision of Uprisings with his theatrical, essayistic and literary works, which clearly imply, even if not thecomplete revision of his earlier views, the incessant development ofcritical reflection on the balance of national spurts and the Silesianidentity. The author reviews and summarizes the most meaningfulrepresentations of this subject by Kazimierz Kutz, the director, theliterary man, the publicist.